PENGARUH SKARIFIKASI DAN MEDIA TUMBUH TERHADAP VIABILITAS BENIH DAN VIGOR KECAMBAH AREN - Muhammad Salim Saleh; Enny Adelina; Endang Murniati; Tati Budiarti (Universitas Tadulako, 2008)
The research aim was to find out the effect of seed scarification and germination substrate upon seed viability and seedling vigor of aren. The research applied a randomized block design with factorial pattern consisting of two factors. The first factor was scarification treatment: without scarification, scarification at 400C, scarification at 400C and soaked in 0.5% KNO3 solution for 36 hours. The second factor was germination substrate: sand, rice hull coal, cocopith, mixture of soil taken from natural palm growth area and organic material at a ratio 1:1, and mixture of 1 g NPK fertilizer with 1 kg soil taken from palm tree forest area and organic material media. The greatest seed germination of 83.33–86.67% with germinating speed of 0.85-1.04 %etmal was found in the scarification at 400C soaking in 0.5% KNO3 solution for 36 hours and soil organic and matter treatment. This treatment also resulted in normal vigorous seed indicated by higher dry content weight and hypothetic vigor index than any other treatments.